Application of Facility and Infrastructure Management in Improving Student Satisfaction - Kholidah Kholidah; Nyong ETIS; Siti Ruchana (International Consortium of Education and Culture Research Studies, 2020)
This paper discusses the impact of facilities and infrastructure management on student’s satisfaction. The success of learning in schools one of which is supported by the facilities and infrastructure of learning. Management of the utilization of educational facilities and infrastructure in schools effectively and efficiently will greatly support the success of the learning process in schools and improve the quality of student’s satisfaction. This research is a descriptive qualitative research which is expected to be able to uncover various information carefully and meaningful analysis-descriptions. Data sources in this study are principal, vice principal also staff of facilities and infrastructure, students too. Data collection bas obtained from interview, observation, and arrangement. As for the data analysis techniques through data reduction, data presentation, and data analysis. The results of the study are expected to be (a) The management of facilities and infrastructure capable improve the implementation of the education process effectively (b) The implementation of management infrastructure and facilities can increase student satisfaction significantly.